Synthesis of Diimidazole Has Pyrazole, Isoxazole and Pyrimidine Derivatives and Evaluation as Antibacterial - Sahar Abdullah Kadham.1, Abdul Jabar Kh. Atia2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
New diimidazole contains pyrazole , isoxazole and thiopyrimidine were synthesized by using simple methods. All compounds were synthesized by using hippuric acid (1) as stating material which was obtained from benzoyl and glycine with. pyrazole derivatives (6a – b ) was obtained from reaction (5a – b) with hydrazine hydrate while reaction of (5a – b )with hydroxyl amine isoxazole derivatives (7a – b) were obtained ,finally reaction of thiourea was reacted with 5a – b thiopyrimidine derivatives were get (8a –b ) . FTIR and 1HNMR spectra were used to characterized derivatives several bacterial species like Pseudomonas aeruginosa , Staphylococcus aureus, and Acinetobacter baumanii were used to tested antibacterial activity